LIMITS TO OPTIONAL DEDUCTIONS AND THE VIOLATION OF TRADE UNION FREEDOM: AN ANALYSIS OF THE UNCONSTITUTIONALITY OF DECREE NO. 741/2023 OF THE MUNICIPALITY OF JUAZEIRO/BA - Brito, Maria Victoria Souza Gonçalves; de Souza Junior , Mario Cleone; Delfim, Priscila Martins (Seven Editora, 2025)
This article examines the unconstitutionality of Municipal Decree No. 741/2023 of Juazeiro/BA, which establishes percentage limits on optional payroll deductions for public servants, under the justification of combating over-indebtedness, but which results in a violation of union autonomy (Article 8, IV, CF/1988). Through bibliographic review and documentary research, focusing on Writ of Mandamus No. 8011579-35.2023.8.05.0146, filed by the Union of Municipal Public Servants of Juazeiro (SINSERP), it analyzes how the decree exceeds the municipal regulatory power, lacking formal law for support. The results highlight the granting of security by the Court of Justice of Bahia in May 2025, overturning a first-instance decision, and demonstrate impacts on the financial management of SINSERP and the sustainability of collective benefits, such as health and dental plans, as well as guaranteeing the sustainability of SINSERP’s activities. Despite the annulment of the decree, the study finds a lack of effective public policies in Juazeiro/BA to curb the over-indebtedness of public employees, perpetuating the cycle. It concludes that specific municipal legislation is needed, reconciling protection of the minimum subsistence level and union rights, with recommendations for future research on debt prevention. DOI: https://doi.org/10.56238/sevened2025.040-007